KERAGAMAN SPESIES DAN KEMIRIPAN KOMUNITAS BURUNG DI AREA REVEGETASI PERUSAHAAN TAMBANG BATUBARA DI KALIMANTAN SELATAN, INDONESIA - Yuda Pranata; Mochamad Arief Soendjoto; Khairun Nisa; Fazlul Wahyudi (Jurnal Sylva Scienteae, 2022)
Birds are easy to find and use to monitor revegetation developments. The purpose of this research was to record bird species found in revegetation areas and to measure species diversity and community similarities. Four locations with different revegetation years in PT Adaro Indonesia, South Kalimantan Province were used as sample locations for data collection in November 2019. Diurnal bird species and the number of individuals were recorded through the pathway and abundance point method. The researcher walked slowly along pathways (inspection road) up to 500 m while observing the left and right of the road within a maximum distance of 50 m. Data collected twice for each location. Data were tabulated and calculated to obtain a diversity indexes (Shannon-Wienner) and community similarity indexes. Of the 35 species (22 families) of birds, 11 species (H '= 2.01) were found in the 2014 revegetation area, 20 species (H' = 1.97) in the 2015 area, 25 species (H '= 2.74) in the 2016 area, and 10 species (H '= 1.18) in the 2017 area. The community similarity index based on species presence ranged from 0.29‒0.65 and based on the number of individuals ranged from 0.41‒0.89. In general, the similarity indexes based on the presence of species are smaller than that based on the number of individuals, although there is exceptional case where the value is greaterBurung mudah sekali ditemukan dan dimanfaatkan untuk memantau perkembangan revegetasi. Tujuan penelitian adalah mendata spesies burung yang ditemukan di area revegetasi serta mengukur keragaman spesies dan kemiripan komunitasnya. Empat lokasi yang berbeda tahun revegetasi di PT Adaro Indonesia, Provinsi Kalimantan Selatan dijadikan lokasi sampel pengumpulan data pada November 2019. Nama spesies burung diurnal beserta jumlah individunya didata melalui metode jalur dan titik kelimpahan. Peneliti berjalan perlahan sepanjang jalur (jalan inspeksi) maksimal 500 m sambil mengamati kiri kanan jalan dalam jarak maksimal 50 m. Pendataan dilakukan 2 kali ulangan untuk setiap lokasi. Data ditabulasi dan dihitung sehingga diperoleh indeks keragaman spesies (Shannon-Wienner) dan indeks kemiripan komunitas. Dari 35 spesies (22 famili) burung, 11 spesies (H’ = 2,01) ditemukan di area revegetasi tahun 2014, 20 spesies (H’ = 1,97) di area tahun 2015, 25 spesies (H’ = 2,74) di area tahun 2016, dan 10 spesies (H’ = 1,18) di area tahun 2017. Indeks kemiripan komunitas berdasarkan pada kehadiran spesies berkisar 0,29‒0,65 dan berdasarkan pada jumlah individu berkisar 0,41‒0,89. Secara umum indeks kemiripan berdasarkan kehadiran spesies bernilai lebih kecil daripada berdasarkan pada jumlah individu, walaupun ada kasus pengecualian yang menunjukkan bahwa nilainya lebih besar